Integrated aquaculture with paddy in fresh and saline water interface of South-West Bangladesh - Alam, MJ; Saha, SB; Islam, ML; Tuong, TP (Bangladesh Journal of Zoology, 2009)
Bangladesh J. Zool. 35(2): 381-389, 2007